Association between the amount of right‐to‐left shunt and infarct patterns in patients with cryptogenic embolic stroke: a transcranial Doppler study. Issue 8 (19th July 2012) - Kim, Ji Won; Kim, Suk Jae; Yoon, Cindy W; Park, Chang‐Hyun; Kang, Kun Woo; Kim, Soo Kyoung; Kim, Yun‐Hee; Bang, Oh Young
<x xml:space="preserve">Abstract</x> Background Paradoxical embolism has been documented as a mechanism of cryptogenic embolic stroke. We investigated the frequency of right‐to‐left shunt in patients with cryptogenic embolic stroke and evaluated the factors associated with diffusion‐weighted imaging (DWI) lesion pattern. Methods We analyzed data on 157 consecutive patients with acute ischemic stroke because of presumed cryptogenic embolism. Agitated saline transcranial Doppler study was conducted in all patients to detect right‐to‐left shunt. We evaluated the association of the amount (microemboli <20 vs. ≥20) and activity (spontaneous vs. after Valsalva maneuver only) of right‐to‐left shunt with diffusion‐weighted imaging lesion patterns. Results Right‐to‐left shunt was observed in 96 (61·1%) patients. The multiplicity and distribution of diffusion‐weighted imaging lesions did not differ depending on the amount and activity of right‐to‐left shunt. However, the size of diffusion‐weighted imaging lesions differed depending on the amount of right‐to‐left shunt (P = 0·019). Right‐to‐left shunt was more frequently observed in patients with small (<1 cm) infarcts than in those with a large infarct (66·7% vs. 45·9%), and most patients with a larger amount of right‐to‐left shunt were found to have small infarcts on diffusion‐weighted imaging (80%). The clinical characteristics, including Framingham stroke risk strategy, did not differ between the groups. Conclusions Our results indicate that the amount of right‐to‐left shunt determines the Diffusion‐weighted imaging lesion patterns and suggest that mechanisms of stroke other than paradoxical mechanism may play an important role in patients with large cryptogenic embolic stroke.